A quantitative assay of peptide-dependent class I assembly. - Elvin, J; Cerundolo, V; Elliott, T; Townsend, A (1991)
We have developed a quantitative assay for the measurement of class I assembly induced by peptide. We have applied this assay to H-2Db, Kb and HLA-A2.1 with a panel of 49 overlapping peptides derived from HIV-1 gag protein. We find that the effects of peptide on assembly form a continuous distribution. By defining positives as those that increase the concentration of folded heavy chains more than three standard deviations from the control we show that 7/48 bind A2.1, 11/49 bind Db and 7/47 bind Kb. The assembly assay contrasts with solid-phase assays in being more discriminating (fewer peptides binding any given class I molecule), and showing less overlap in the patterns of peptides bound by the three class I molecules.